Review paperHyperglycaemia and Inflammation are culprits of late diabetic complications - Zozulińska, Dorota; Wierusz-Wysocka, Bogna (Archives of Medical Science, 2005)
Hyperglycaemia and the inflammatory process play a crucial role in the development of late diabetic complications. In hyperglycaemic conditions glucose metabolism is enhanced in both main and alternative pathways. It results in enhanced glycation of proteins, glucose autoxidation and overproduction of reactive oxygen species (ROS). Metabolic disturbances lead to activation of protein kinase C (PKC) and nuclear factor kappa B (NF- k B). NF- k B is a transcription factor that itself activates many proinflammatory genes in the vasculature. Traditional risk factors such as elevated LDL cholesterol, low HDL cholesterol level, smoking, hypertension and hyperglycaemia do not fully explain the marked increase in mortality associated with diabetes and its complications. Many novel factors, named non-traditional cardiovascular disease risk factors, have been proposed recently as potentially important predictors of coronary heart disease both in general and diabetic population. Most of them are characteristic of the inflammatory process and reflect intensity of inflammation although experimental, clinical and epidemiological studies suggest that some processes related to low-grade inflammation may be relevant to diabetic micro- and macroangiopathy, further large-scale observational studies and randomized intervention studies of “anti-inflammatory” interventions will be needed to elucidate the meanings of these associations.